Ultrawideband Harmonic Suppression in Microstrip Patch Antenna Using Novel Defected Ground Structures - Jun Fan; Jiangchuan Lin; Feng Qin; Jinliang Cai; Mingxu Kan (International Journal of Antennas and Propagation)
Suppressing higher-order modes up to sixth harmonics of the fundamental working frequency in a single-layer microstrip line-fed patch antenna has been successfully demonstrated. Higher-order modes of the antenna are suppressed by simultaneously employing a circular head open stub connected to the feed line and a novel defected ground structure (DGS) beneath the feed line. The filtering property of the antenna has been improved by the novel DGS significantly. The role played by the novel DGS is carefully analyzed, and the effect of some key parameters of DGS is further discussed. A microstrip patch antenna with the working frequency 3.13 GHz (fc) is designed and manufactured. The designed antenna possesses an ultrawideband harmonic suppression capability ranging from 2fc to 6fc. More importantly, the area occupied by the novel DGS is decreased by 41% compared to the earlier design.